(untitled) (Journal of the College of Education for Women, 2019)
Abstract:The aim of the present research is to evaluate the child’s nutritionalmethod (2-5 years old) which is based on his resistance of the food highly richwith nutritional elements and his acceptance of the food of a low nutritionalvalue in addition to his having forbidden food with other mates and makinguse of all mates when having food, in establishing the sound social values andaffection since child hood. The required statistical equation have been usedby the researcher namely (Z test).The sample of the present study consists of (26) children who were selectedintentionally and randomly from the kindergartens of Al-Bayaa region and thecollege of Education for women. The questionnaires were distributed amongthe samples mother. After sorting the answers, it was noticed that the foodsrefused by the child included : milk, eggs, meat, fish, rice, potatoes, soup,bread, eggplants, green pepper, cucumber, tomatoes, banana and orange.The reasons behind the children’s refusal mediated between the highestpercentage (100%) for the children who had no desire and the lowestpercentage (20%) for fear of the shape of food as a fish for not having suchtypes of food by the cartoon films, while the other percentages (30-80%)oscillated for the food taste, lack of appetite, inability to crew, food smell,creating accuses, the child’s health but when the child was brought togetherwith his mates, he was able to have the same rejected food in a high degree.The results of the study concluded that the increase of the child’s acceptanceof the food leads to some positive indicators among which achieving thesound social, educational and nutritional aims especially under thecircumstances our country lives in and this is the first step towardsestablishing the national values for the children of the neighborhood and thekinder gather friends away from any wrong concept that might dissociatethem.